Effects of gentamicin on spontaneous and agonist-induced in vitro contractions of isolated myometrial tissue from pregnant cows - Yuksel, Murat; Ocal, Halts; Ayar, Ahmet (Polish Soc Veterinary Sciences Editorial Office, 2020)
The aim of the present study is to examine the effects of gentamicin sulphate on spontaneous, oxytocin and PGF(2 alpha) induced in vitro contractions of myometrium isolated from pregnant cows. Myometrial strips were obtained from healthy pregnant cows and suspended in a covered organ bath filled with Krebs' solution at 37 degrees C (pH 7.4) continuously bubbled with 95% oxygen and 5% carbon dioxide: isometric contractions were recorded using an isometric force displacement transducer. After the stabilization of spontaneous contractile activity during a 90-minute equilibration period, contractions were recorded for 20 minutes (control). Gentamicin sulphate was then added to the tissue bath cumulatively and the responses were recorded every 20-minutes for each consecutive dose of gentamicin. In agonist-induced contractions, oxytocin or PGF(2 alpha) was added to the tissue bath at the end of the equilibration period and the same protocol was followed to investigate the effects gentamicin on these agonist-induced contractions. Gentamicin decreased the frequency and inhibited the amplitude of the spontaneous contractions in a dose dependent manner (p < 0.05). The mean frequency and amplitude of oxytocin-induced contractions was significantly inhibited by the application of gentamicin (p < 0.05). Gentamicin also inhibited the contractions induced by PGF(2 alpha) in a dose dependent manner (p < 0.05). This study showed gentamicin inhibited, depending on the dosage, oxytocin and PGF(2 alpha) induced contractions of myometrium isolated from pregnant cows. Upon clinically examining the findings obtained by the study, gentamicin can be used as an antibacterial in septic abort and chorioamniotis in order to prevent premature birth, abortion and early uterus contractions. Further studies are necessary to test whether the same effect will take place in vivo and to examine the effects of long-term use of gentamicin on offsprings.
Keywords: gentamicin; bovine; myometrium; contractility; oxytocin; PGF(2 alpha)